New leaf fall disease in rubber-pathogen characterization and rubber clone resistance evaluation using detached leaf assay - MUHAMAD RIZQI DAROJAT; SINTHO WAHYUNING ARDHIE; FETRINA OKTAVIA; SUDARSONO SUDARSONO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Darojat MR, Ardhie SW, Oktavia F, Sudarsono. 2023. New leaf fall disease in rubber-pathogen characterization and rubber clone resistance evaluation using detached leaf assay. Biodiversitas 24: 1935-1945. Leaf fall disease (LFD) has become a significant issue for rubber plantations worldwide. Over the last four years, a newly emerging LFD has posed an alarming problem in natural rubber production. The most efficient way to control LFD is to use resistance rubber clones. Therefore, this study aims to characterize the pathogen causing the newly emerging LFD and evaluate rubber clone resistance to the pathogen using detached-leaf assay. The fungal pathogens were isolated from 32 F1 progenies of PB 260 x SP 217 crosses, and the fungi were characterized and identified based on their morphological and molecular characteristics. The results showed that the isolated pathogen causing LFD was Neopestalotiopsis sp. Although they were all pathogenic, the arrays of isolated fungi exhibited various degrees of virulence, and P-212 was the most virulent fungal isolate. The resistance evaluation showed that rubber clones, isolates, and rubber clones by isolate interactions had a significant (p<0.05) effect on the lesion-symptom diameters. Based on the lesion diameter responses, the IRR 112 and RRIC 100 rubber clones were resistant to Pestalotiopsis sp. since they only showed less than 10 mm lesion diameters. The IRR 39 and PB 260 rubber clones were susceptible and showed more than 20 mm lesion diameters. The detached-leaf assay can easily screen rubber clones' responses to the fungi causing LFD. The resistance evaluation results can assist future rubber breeding strategies for the newly emerged LFD-resistant characters.